Molecular characterization of staphylococcus aureus from nosocomial sources by multilocus enzyme electrophoresis (mlee) (2002)
Multilocus Enzyme Electrophoresis (MLEE) was used to characterise 41 Staphylococcus aureus isolates taken from Hospital San Juan de Dios (Bogotá) patients and personnel at the Intensive Care Unit (ICU), from September 1998 to September 1999. The genetic relationships between isolates, as well as resistance profile influence, biotype and compilation time/date, were established. The experimental evidence suggests that the population structure corre-sponds to the clonal model described for Staphylococcus aureus populations, reflecting the prevalence of a small number of clones during the collection period.